PENGEMBANGAN MEDIA KOMIK MATERI PERKALIAN MATA PELAJARAN MATEMATIKA - Muhammad Syafiul Maula; Yulina Ismiyanti (Cahaya Smart Nusantara, 2025)
The issue of digitalization in education highlights the need for innovative learning media that can adapt to technological advances and students’ needs. This study aims to develop a comic-based learning media to support the teaching of multiplication in elementary mathematics. The research method employed is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation was carried out by three experts: a media expert, a content expert, and a language expert. The results of the validation indicate that the developed comic received an average score of 92% from each expert, which falls into the